Inflation-unemployment tradeoff and regional labor market data - Uwe Hassler; Michael Neugart (Technische Universität Darmstadt, Department of Law and Economics, 2002)
We estimate a linear and a piecewise linear Phillips curve model with regional labor market data for West German and Neue Länder. Employing regional observations allows us to country difference the data. This eliminates, under the assumption of homogeneous Länder, supply shocks and changes in the formation of expectations as possible identification failures. With seemingly unrelated regressions we find a flat Phillips curve in the Neue Länder. For the West German Länder a piecewise linear model with a higher inflation-unemployment tradeoff for the regime of low unemployment rates fits the data very well. The results hold true if we control for endogeneity of the unemployment rate. With a kinked but upward sloping aggregate supply curve there seems to be room for stabilization policies, at least in the range of aggregate demand shifts that our data covers.
Keywords: E24; E31; 330; inflation-unemployment tradeoff; NAIRU; regional labor market data; seemingly unrelated regression; Phillips-Kurve; Natürliche Arbeitslosigkeit; Regionaler Arbeitsmarkt; Regression; Schätzung; Alte Bundesländer; Neue Bundesländer